Social and Economic Aspects of the Transmission of Pathogenic Bacteria between Wildlife and Food Animals: A Thematic Analysis of Published Research Knowledge. (22nd January 2015) - Fournier, A.; Young, I.; Rajić, A.; Greig, J.; LeJeune, J.
Summary Wildlife is a known reservoir of pathogenic bacteria, including Mycobacterium bovis and Brucella spp. Transmission of these pathogens between wildlife and food animals can lead to damaging impacts on the agri‐food industry and public health. Several international case studies have highlighted the complex and cross‐sectoral challenges involved in preventing and managing these potential transmission risks. The objective of our study was to develop a better understanding of the socio‐economic aspects of the transmission of pathogenic bacteria between wildlife and food animals to support more effective and sustainable risk mitigation strategies. We conducted qualitative thematic analysis on a purposive sample of 30/141 articles identified in a complementary scoping review of the literature in this area and identified two key themes. The first related to the framing of this issue as a 'wicked problem' that depends on a complex interaction of social factors and risk perceptions, governance and public policy, and economic implications. The second theme consisted of promising approaches and strategies to prevent and mitigate the potential risks from transmission of pathogenic bacteria between wildlife and food animals. These included participatory, collaborative and multidisciplinary decision‐making approaches and the proactive incorporation of credible scientific evidence and local contextual factors into solutions. The integration of these approaches to address 'wicked problems' in this field may assist stakeholders and decision‐makers in improving the acceptability and sustainability of future strategies to reduce the transmission of pathogenic bacteria between wildlife and food animals.